Morphological feature and mapping inflammation in classified carotid plaques in symptomatic and asymptomatic patients: A hybrid 18F-FDG PET/MR study - Zhang, Yue; Cui, Bixiao; Yang, Hongwei; Ma, Jie; Yang, Yu; Yang, Bin; Ma, Yan; Jiao, Liqun; Li, Xiang; Lu, Jie (Frontiers in Neuroscience, 2023)
Purpose To investigate morphological and inflamed-metabolism features of carotid atherosclerotic plaques between symptomatic and asymptomatic patients with hybrid 18F-FDG PET/MR imaging. Methods A total of 20 symptomatic and 20 asymptomatic patients with carotid plaques underwent hybrid 18F-FDG PET/MR scans. American heart association (AHA) lesion types were classified, and plaque compositions were further determined on consecutive MRI axial sections in both carotid arteries. 18F-FDG uptake in carotid arteries was quantified using region of interest (ROI) methods based on maximum standardized uptake values (SUVmax) and target-to-background ratio (TBR) on corresponding positron emission tomography (PET) images. Results A total of seventy-one carotid plaques were quantified. AHA type VI was the most common (23, 32.4%), and the region of carotid bifurcation was the most common place presenting lesions (32, 45.1%). Compared with the asymptomatic group, the prevalence of high-risk features including plaque burden, lumen stenosis, maximum necrotic core area, and maximum intra-plaque hemorrhage area increased in the symptomatic group. Carotid TBR values of plaque in symptomatic group (TBR = 2.56 ± 0.34) was significantly higher than that in asymptomatic group (TBR = 1.57 ± 0.14) (P < 0.05). hs-CRP is an independent risk factor for the stability of carotid plaque. The correlation between normalized wall index (NWI) and TBR values was significantly positive in both the symptomatic and the asymptomatic groups (P < 0.01), and both NWI and TBR were significantly correlated with the level of hs-CRP (P < 0.01). Conclusion Integrated 18F-FDG PET/MR scans presented distinct risk features between symptomatic and asymptomatic patients. Hybrid 18F-FDG PET/MR systems combined with clinical serum hs-CRP may help distinguish vulnerable carotid plaques.